Pemanfaatan Grand Desain UIN Gusdur untuk Kemajuan Keilmuan Global dan Persoalan Kemanusiaan - Batsnah Nuwaifila (Al-Bustan: Jurnal Pendidikan Islam, 2024)
When  examining  the  history  of  science  and  religion,  there  are  sacred  texts  that  have  been interpreted in a way that separates science and religion, leading to confusion in various fields at the time. This separation between science and religion arose due to misunderstandings in interpreting the universal teachings of Islam. Efforts to unify science and religion are currently being  pursued,  particularly  in  the  field  of  education  in  Indonesia.  This  study  employs  a descriptive qualitative research method with a library research approach. The purpose of this study  is  to  serve  as  a  benchmark  for  educational  institutions  in  developing  their  scientific knowledge in line with advancements inthe field of education. This research is important for the  development  of  the  Islamic  State  University  KH.  Abdurrahman  Wahid  in  its  pursuit  of becoming  a  more  advanced  university.  The  result  of  this  study  is  that  the  utilization  of  the grand design of UINGus Dur can be achieved through the dynamization of Islamic thought as an effort to reinterpret Islamic teachings in a way that allows for a more dynamic response to contemporary  Islamic  issues.  In  addition,  the  utilization  of  facilities  and  the  development  of curricula are necessary to improve the quality of education within the university.